The ICT resemantization of the humanist culture - José Antonio Marín-Casanova (Index Comunicación, 2018)
This paper essays a hermeneutical reflection on the repercussion of the ICT phenomenon in the notion of “culture”, which is resignifying what today means to be an “educated” person. In particular, we try to find out the reasons explaining why the elevated education model, linked secularly to the modern project of humanism, has become inoperative. The objective is to understand that ICT are the factum of our time and precisely because they are modifying the criteria of human readability. Thus, the consequences of the inversion of the means-ends relationship inherent to the globalization of ICT are problematized. This fact no longer allows the reading of the human being as a subject and of the technique as an instrument at “his” axiological disposal, which requires reviewing the categories of humanism. It is concluded by noting the correspondence between the neotechnological fact and the “mass-man”, whose indifference to the “cult” displaces the old “humanistic” cult/barbarian opposition to the cult/specialized one. And, in the face of mass culture or coolture as neobarbarism of specialization, it is proposed to redefine the cult human as a specialist almost in a cinematographic sense, as the “double”, specialist in generalities, who knows how to return any allegedly necessary or unique discourse to its genuine contingency.